Considerations regarding the association: Cooperation of small and medium fruit producers - Ancuţa Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Between March 2017 and April 2017, ICEADR Institute conducted a survey among the Romanian fruit producers, in order to identify the problems they face and to highlight their opinions. The survey's results were used to find solutions for an efficient exploitation of fruits' production. Quantitative research was used as the main method for picking information while the research technique consisted on the structural research (survey). Most farmers are not implied in associative forms and they are not interested in joining one in the nearest future. Small exploitations register small productions which do not permit them to sign selling contracts and consequently their incomings are around 4500 RON each year. Also, the Authorities' implication in supporting small and medium producers is very low. Awareness of the advantages of association / cooperation by facilitating access to private and public resources, promoting practices and technologies that ensure environmental protection, assurance of consultancy, defense of members' interests in their relations with government bodies and state administration, promotion of products on national and international market , ensuring equal rights for all members, improving the information and supply system, developing agro-food markets, correlating the level of production and product quality in line with market requirements, capitalizing on larger quantities of products, reducing tax evasion is the solution to solving problems Romanian grain farmers.
Keywords: L11; Q11; O13; 330; association; cooperative; producers; EU funds; funding